Advanced control approach for solar assisted electric vehicle drive. (2021) - Akhtar, Iram; Kirmani, Sheeraz; Hasan, Shaheen; khan, Sabah
Abstract: Presence of the solar energy sources in energy combination is the fastest developing movements in all over the world to decrease the reliance on fossil fuels re-serves. Whereas, the increase in the oil prize and pollution problems has forced to develop the electric vehicle with solar energy system. This work discusses the control of solar powered induction motor drive with advanced control approach. The overall system permits good control operation of induction motor drive through advanced architecture that allows the consumption of accessible solar power at most of the time. The complete system consists of a boost converter for maximum power taken from solar energy system and to regulate the dc link volt-age, advanced rapid predictive pulse width modulated three phase inverter to control the three phase induction motor drive. The efficiency parameters of the three phase inverter are primarily dependent on the control approaches used to regulate the inverter. In this paper, the advanced rapid pulse width modulation technique is used for regulating the inverter as it can regulate the input of the induction motor according to the functions. Therefore, modelling and simulation of the solar assisted electric vehicle with induction motor has been presented with advanced control approach.